THE IMPORTANCE OF ADVICES AND TEACHINGS IN THE BOOK “TA’LIM AL-MUTA’ALLIM” (The Journal of Interdisciplinary Human Studies, 2026)
This article examines “Taʼlim al-mutaʼallim,” the celebrated work by the Islamic scholar Burkhaniddin al-Zarnuji (12th–13th centuries AD), focusing on the essential manners, advices, and instructions for acquiring knowledge presented therein. The study analyzes how al-Zarnuji substantiates his pedagogical recommendations through reliable primary sources – including Quranic verses, prophetic hadiths, and the counsel of eminent scholars such as Imam Aʼzam Abu Hanifa. The article demonstrates that this foundational text on the path to knowledge remains highly relevant to contemporary educational discourse, addressing issues such as the education of women, financial support for students, the importance of consultation, and the ethics of intellectual perseverance.
Keywords: Taʼlim al-mutaʼallim; hadith; ilmu hal; Abu Hanifa; complete person; wajib, advice; Burkhaniddin al-ZarnujI; Islamic pedagogy